Analysis of Robusta Coffee Supply Chain Management in Tutur District, Pasuruan Regency - Rafli Septian Dwi Antoro; Sri Tjondro Winarno; Pawana Nur Indah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Tutur District is the center of Robusta coffee production in Pasuruan Regency. Robusta coffee supply chain management activities in Tutur District are generally very interesting for in-depth exploration and study. Robusta coffee supply chain management activities by robusta coffee farmer groups have various paths. In addition, it is suspected that there are variations in the production scale of Robusta coffee commodities, so that they have different marketing channels according to the demand and limited supply of Robusta coffee. In this study, the population selected were 7 robusta coffee farmer groups and the sample used was 35 coffee farmers. This research uses purposive sampling method. Robusta coffee supply chain performance is measured using the Food Supply Chain Network approach. The analytical method used is marketing margin and farmer's share. Based on the research results, it is known that the condition of the robusta coffee supply chain runs smoothly and the robusta coffee marketing channel shows that the marketing margin with low value is in marketing channel 1 but has a high level of farmer's share value.